SAT0415 Performance of Anti-Nuclear Antibodies (ANA) for Classifying Systemic Lupus Erythematosus (SLE): A Systematic Literature Review and Meta-Regression of Diagnostic Data. (9th June 2015) - Leuchten, N.; Brinks, R.; Hoyer, A.; Schoels, M.; Aringer, M.; Johnson, S.; Schmajuk, G.; Daikh, D.; Dörner, T.; Bertsias, G.
Abstract : Background: EULAR and ACR have jointly funded a project to improve existing SLE classification criteria, aiming at earlier and more accurate classification of the disease. This abstract reports on an early phase of that project. ANA constitute the immunological hallmark of SLE, and ANA testing is widely used for SLE diagnosis based on its reportedly high sensitivity. Although indirect immunofluorescence on Hep-2 cells (IIF-Hep2) is considered the gold standard of ANA testing (1), the performance of different ANA titers and the possibility to include ANA as entry criterion for the classification of SLE have not been systematically evaluated. Objectives: To review the published literature on the performance of IIF-Hep2 ANA testing for the classification/diagnosis of SLE. Methods: A systematic literature search was conducted in MEDLINE and EMBASE for articles published between January 1990 and March 2014. The research question was structured according to PICO (Population, Intervention, Comparator, Outcome) format rules, and PRISMA recommendations were followed where appropriate. Meta-regression analysis for diagnostic tests was performed using the ANA titer as independent variable and sensitivity and specificity as dependent variables. Results: A total of 3, 919 publications were screened in abstract and title and 623 articles were evaluated in full-text. Of these, 60 matched the eligibility criteria and were included in the analysis. The included studies comprised 10, 089 SLE patients in total, of whom 9, 587 (95.0%) were reported to be ANA positive at various titers. For ANA at titers of 1:40, 1:80 and 1:160, meta-regression gave sensitivity values of 98.8% (95% confidence interval [CI] 98.0-99.3%), 98.1% (CI 97.1-98.8%) and 95.4% (CI 93.0–97.0%), respectively. The corresponding specificities were 75.1% (CI 64.3-83.5%), 83.3% (CI 74.9-89.3%) and 93.2% (CI 88.6-96.0%), respectively. Conclusions: The results of this systematic literature search and meta-regression confirm the high sensitivity of a positive ANA test for SLE. While no decision has so far been made, these data suggest that ANA at a titer of 1:80 could be a reasonable entry criterion for SLE classification criteria. References: Agmon-Levin et al, Ann Rheum Dis 2014; 73: 17ff Disclosure of Interest: None declared